Sistem Kendali Sudut Pitch Projector Headlamp Sepeda Motor Berbasis Closed Loop System - Cipto Bagus Jati Kusumo; Dahnial Syauqy; Wijaya Kurniawan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
The main lights of the motorcycle illumination in the country of Indonesia generally use Halogen gas which results from less illumination for the minimal road PJU (Street Lighting), with the creativity of the vehicle users then the source of lighting replaced with sources that produce more light. Like the example of lights that use Xenon gas or commonly known as High Intensity Dishcharge Xenon, but with the replacement of this, new problem emerging, light emitting wildly dazzling other road users. The use of the Headlamp Projector is the only one to avoid the dazzling glare of the wild light by focusing only on the road, the beam of focusing light must be set to road so that the focus does not lead to other road users. Therefore, this system is built to facilitate the driver in setting the focus of the light beam.The system works with the help of IMU MPU6050 sensor and all 6 axis, actuator mechanism on the motorcycle headlamp and Closed Loop System controlling methode. The current angle value read by the sensor is then set aside with the value of the set points that have been in the previous calculation, the result of the difference is then made reference by the system to control the actuator that will affect the pitch angle of the headlamp. The success rate of this system is 98.154% of the six attempts to adjust the altitude of light beam with different passenger loads on the same motorcycle.